SHARIAH PORTFOLIO MODEL WITH STOCHASTIC PURIFICATION ANDPROBABILISTIC ASSET SCREENING CONSTRAINTS - Chairina, Muthia
Abstract. The growth of Islamic financial assets has grown since 2012 and is expected to continue rising in 2024. This thesis researches the optimization of Shariah portfolios using stochastic purification processes and probabilistic constraints in asset screening. The stochastic purification process aims to reduce investment returns from non-permissible income. Subsequently, the probabilistic constraints in asset screening are designed to ensure compliance with Shariah principles. The obtained results consist of numerical simulations, specifically the efficient frontier of the model categorized into two cases: the Markowitz portfolio and the mean-variance of the Shariah model. Furthermore, the Shariah portfolio screening process is divided into two cases, using cash ratio threshold values of u1 = 0.45 and u1 = 0.3. Shariah portfolios are categorized based on financial ratio screening with Normal and Beta-distributed. From these cases, it is observed that, for the same return, the Shariah portfolio screening with a threshold of u1 = 0.3 has higher risk compared to the Shariah portfolio screening with a threshold of u1 = 0.45. For an equivalent return, the Beta-distributed financial ratio screening portfolio is also riskier compared to the Normal-distributed. Furthermore, it is deduced that as the desired return increases, the associated risk also amplifies.